Автоматизация процесса выявления радикулоишемии на ранней стадии развития - Черкасова, Е. А. (ХНУРЭ, 2017)
We offer to create a system for the automation of the development of radiculo-ischemia in the early stages of the development of the disease by using modern methods and means. The structure of the offered system is developed using UML modeling standards, that implies further use of structured programming and client-server technologies SQL. As an environment for the development Visual Studio's object-oriented design system is planned to be selected.
Keywords: биомединженерия